The Forum Theatre in the prevention of exclusion from a peer group in the school space - Forysiewicz, Barbara (Journal of Education Culture and Society, 2020)
Aim. The article is a report from the research conducted in 2017 during the Forum Theatre performance, and it demonstrates the possibilities of using the Forum Theatre of Augusto Boal in activities to prevent exclusion from the peer group of teenage students. The purpose of this article is to signal the possibility of using the idea of ​​ Boal in preventing exclusions in the school space. Methods. In order to discuss the problems, the analysis of source material and participant observations were used. Results. At Forum Theatre, young people reveal their worldview and value system by interacting with actors and performing stage activities. The teacher, observing the students actions in the performance, can assess their empathy, sensitivity and interpersonal competence. The teacher gets to know the qualities that affect the student’s mental state at the time of exclusion from the peer group. In the theatrical activity, the personality of the student with his or her predisposition to being a victim or torturer is revealed. Using the example of the analysed spectacle The Cage directed by Jarosław Rebeliński in 2017, it is clearly seen that the Forum Theatre makes it possible to get to know the student, and thus his or her problems in relation with peers. Forum Theatre shows the effects and causes of exclusion while simultaneously signalling to the teacher the symptoms of the problem manifesting themselves in the behaviour of young people. Conclusion. Forum Theatre can be a diagnostic method for teachers in activities preventing the exclusion of a student from a peer group at school. Forum Theatre can be used as a method of working with students at risk of exclusion due to intolerance, lack of acceptance or lack of developed communication skills.